Surface molecule CD229 as a novel target for the diagnosis and treatment of multiple myeloma - Atanackovic, Djordje (Ferrata Storti Foundation, 2011)
BACKGROUND: To date, multiple myeloma remains an incurable malignancy due to the persistence of minimal residual disease in the bone marrow. In this setting, monoclonal antibodies against myeloma-specific cell surface antigens represent a promising therapeutic approach, which is however hampered by a lack of appropriate target structures expressed across all pathogenic myeloma cell populations. We, therefore, investigated functionally relevant immunoreceptors specifically associated with myeloma cells as well as their clonogenic precursors. DESIGN AND METHODS: Potential target proteins were identified using antibody arrays against phosphorylated immunoreceptors with lysates from myeloma cell lines. CD229 expression was confirmed in primary myeloma cells by reverse transcriptase polymerase chain reaction, western blot, fluorescence-activated cell sorting, and immunohistochemistry. Apoptosis, clonogenic growth, and sensitivity to chemotherapy were determined following short-interfering RNA-mediated downregulation of CD229. Antibody-dependent cellular and complement-dependent cytotoxicity were analyzed using a monoclonal antibody against CD229 to demonstrate the antigen’s immunotherapeutic potential. RESULTS: Our screening assay identified CD229 as the most strongly over-expressed/phosphorylated immunoreceptor in myeloma cell lines. Over-expression was further demonstrated in the CD138-negative population, which has been suggested to represent myeloma precursors, as well as on primary tumor cells from myeloma patients. Accordingly, CD229 staining of patients’ bone marrow samples enabled the identification of myeloma cells by flow cytometry and immunohistochemistry. Down-regulation of CD229 led to a decreased number of viable myeloma cells and clonal myeloma colonies, and enhanced the anti-tumor activity of conventional chemotherapeutics. Targeting CD229 with a monoclonal antibody resulted in complement- and cell-mediated lysis of myeloma cells. CONCLUSIONS: Our results demonstrate that the immunoreceptor CD229 is specifically over-expressed on myeloma cells including their clonogenic precursors and contributes to their malignant phenotype. Monoclonal antibodies against this protein may represent a promising diagnostic and immunotherapeutic instrument in this disease.